Azelaic Acid Exerts Antileukemic Activity in Acute Myeloid Leukemia - Pan, Yunbao; Liu, Dong; Wei, Yongchang; Su, Dan; Lu, Chenyang; Hu, Yanchao; Zhou, Fuling (Frontiers in Pharmacology, 2017)
Acute myeloid leukemia (AML) is an acute leukemia common in most adults; its prevalence intensifies with age. The overall survival of AML is very poor because of therapeutic resistance. Azelaic acid (AZA) is non-toxic, non-teratogenic, and non-mutagenic and its antitumor effect on various tumor cells is well established; Nonetheless, its therapeutic effects in AML cells are largely unknown. In this study, it was shown that AZA significantly inhibits the cell viability and induces apoptosis in AML cells in a dose-dependent manner. Additionally, AZA suppressed the expression of phosphorylated Akt, Jab1 andTrx , and this suppression was enhanced by treatment with Jab1 siRNA. Furthermore, AZA sensitized AML cells to Ara-c chemotherapy. The suppressive effect of AZA on tumor growth was examined in vivo by subcutaneously inoculated AML cells in a tumor model using nude mice. These findings indicate that AZA is useful as an effective ingredient in antineoplastic activity.